Relationship between Knowledge, Information, and School Sanitation Facility with Menstrual Hygiene Practices Among Schoolgirls - Megara Maritza Tabina (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Menstrual hygiene practices are a form of self-care mainly related to mantaining the hygiene of reproductive organs specifically during menstruation. Based on previous research there are still various challenges for students to be able to maintain their menstrual hygiene in school, these challenges includes knowledge about menstruation, information, as well as school sanitation facility. Objective: The study aims to identify the relationship of knowledge, information, and school sanitation with menstrual hygiene practices in junior highschool students. Method: This study uses cross sectional carried out at one of Juniorhigh School in Wonokromo, Surabaya. The population in this study was a total of 45 girls, and the sample used 41 girls. The data analysis method is descriptive and analytical, using a chi-square test with (?=5% or 0.05) to identify the relationship of knowledge, information, and school sanitation facility with student menstrual hygiene practices. Result: The results of the study showed that 29 girls (71%) have good menstrual hygiene practices, and 12 other girls (29%) have poor menstrual hygiene practices. 32 girls (78%) stated that menstrual higiene information in the school was adequate and 9 girls (22%) said that the school's menstrual hygiene information was insufficient. Furthermore, 32 girls (78%) stated that school sanitation facilities were sufficient and could support the implementation of the Menstrual Hygiene Management (MHM), while the other 9 girls (22%) stated that the school hygiene facilities weren't sufficient for girls. The results of the bivariable analysis shows that there are meaningful relationships between knowledge, information and school sanitation facility with menstrual hygiene practices. Conclusion: This study shows the relationship between knowledge, information, and school sanitation facility with menstrual hygiene practices among schoolgirls.